2021
DOI: 10.1016/j.ekir.2020.12.018
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Pooled Analysis of Roxadustat for Anemia in Patients With Kidney Failure Incident to Dialysis

Abstract: Introduction Erythropoiesis-stimulating agents are associated with increased cardiovascular risk when higher doses are used toward higher hematocrit targets. Patients new to dialysis are at higher risk for morbidity and mortality. Systematic evaluation of this population was predefined in the roxadustat clinical development program. Roxadustat is a hypoxia-inducible prolyl hydroxylase inhibitor. Methods Data were pooled from 3 phase 3, randomized, open-label, active-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
2
36
0
4
Order By: Relevance
“…In the pooled analysis of patients with DD-CKD, the time to first MACE was similar for roxadustat vs. epoetin (HR, 1.02 [95% CI: 0.88, 1.20]), which met the definition for noninferiority. 41,42 In a prespecified subset analysis of 1,526 incident dialysis patients, J o u r n a l P r e -p r o o f treatment with roxadustat was noninferior to epoetin in MACE (HR, 0.82 [95% CI: 0.60, 1.11]) 42,43 . The overall rate of adverse events (AEs) was similar between roxadustat-and epoetin-treated patients (at least one AE in 86.6% vs. 86.0%) in the pooled DD-CKD analysis.…”
Section: Results Of Hif-phi Clinical Studiesmentioning
confidence: 99%
“…In the pooled analysis of patients with DD-CKD, the time to first MACE was similar for roxadustat vs. epoetin (HR, 1.02 [95% CI: 0.88, 1.20]), which met the definition for noninferiority. 41,42 In a prespecified subset analysis of 1,526 incident dialysis patients, J o u r n a l P r e -p r o o f treatment with roxadustat was noninferior to epoetin in MACE (HR, 0.82 [95% CI: 0.60, 1.11]) 42,43 . The overall rate of adverse events (AEs) was similar between roxadustat-and epoetin-treated patients (at least one AE in 86.6% vs. 86.0%) in the pooled DD-CKD analysis.…”
Section: Results Of Hif-phi Clinical Studiesmentioning
confidence: 99%
“…Roxadustat has been investigated for the treatment of anemia associated with chronic kidney disease in three global phase 3 trials and is approved in this indication in China and Japan (85,86). Pooled analyses of phase 3 studies comparing roxadustat with placebo in patients with non-dialysis-dependent chronic kidney disease and with epoetin alfa in dialysis-dependent patients showed that roxadustat was at least as efficacious in correcting anemia and had a better cardiovascular safety profile compared with placebo and epoetin alfa (87). Notably, a separate phase 3 trial in patients undergoing dialysis in China found that, unlike epoetin alfa, which increased hemoglobin levels to a greater extent in patients with normal C-reactive protein (CRP) levels compared with those with elevated CRP levels, the hemoglobin response with roxadustat appeared to be unaffected by CRP levels (a marker of inflammation) (44).…”
Section: Roxadustatmentioning
confidence: 99%
“…47 The global phase 3 program for roxadustat includes 4 studies in NDD-CKD patients (ALPS, ANDES, and OLYMPUS using placebo control; DOLOMITES using ESA control) and 4 studies in DD-CKD patients (HIMALAYAS, ROCKIES and SIERRAS using epoetin control; PYRENEES using epoetin or darbepoetin control). The first two publications 48,49 from the roxadustat global phase 3 program appeared in Kidney International Reports in 2021, accompanied by an editorial. 50 In the ANDES study of NDD-CKD patients 48 915 subjects were randomized 2:1 to roxadustat or placebo.…”
Section: Roxadustatmentioning
confidence: 99%
“…95% CI:0.57-1.18). 49,55 Among DD-CKD patients in the pooled analysis, the rate of AE and hyperkalemia was similar in the two groups, although arteriovenous fistula thrombosis rate (5.2 vs. 3.9 per 100 patient-years), deep vein thrombosis (0.7 vs. 0.2 patient-years) and seizures (2.0 vs. 0.7%) were all higher in the roxadustat-vs. epoetin-treated patients, respectively. 53 In the European PYRENEES phase 3 study of 838 DD-CKD patients treated with roxadustat or ESA for 52-104 weeks, roxadustat demonstrated noninferiority in maintaining stable Hb levels and superiority in LDL cholesterol reduction from baseline and reduction in IV iron use.…”
mentioning
confidence: 91%